2022
DOI: 10.1111/nyas.14807
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus adhesion to the host

Abstract: Staphylococcus aureus is a pathobiont capable of colonizing and infecting most tissues within the human body, resulting in a multitude of different clinical outcomes.Adhesion of S. aureus to the host is crucial for both host colonization and the establishment of infections. Underlying the pathogen's success is a complex and diverse arsenal of adhesins. In this review, we discuss the different classes of adhesins, including a consideration of the various adhesion sites throughout the body and the clinical outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 199 publications
0
8
0
Order By: Relevance
“…Staphylococcus aureus is a colonizing opportunistic pathogen causing infections when the host’s immune defenses are breached ( 1 ). The cell wall-anchored surface (CWA) proteins of S. aureus are important virulence-associated factors that support processes such as immune evasion, iron acquisition, biofilm formation, and host adhesion ( 1 3 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Staphylococcus aureus is a colonizing opportunistic pathogen causing infections when the host’s immune defenses are breached ( 1 ). The cell wall-anchored surface (CWA) proteins of S. aureus are important virulence-associated factors that support processes such as immune evasion, iron acquisition, biofilm formation, and host adhesion ( 1 3 ).…”
mentioning
confidence: 99%
“…Staphylococcus aureus is a colonizing opportunistic pathogen causing infections when the host’s immune defenses are breached ( 1 ). The cell wall-anchored surface (CWA) proteins of S. aureus are important virulence-associated factors that support processes such as immune evasion, iron acquisition, biofilm formation, and host adhesion ( 1 3 ). CWA proteins adhere to different molecules and surfaces within the body, and consequently contribute to the ability of S. aureus to cause a multitude of different diseases ( 1 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…S1) ( 52 ). While this analysis indicated that there were not any differences in the carriage of genes with known roles in biofilm, such as polysaccharide intracellular adhesin, proteases, or clumping factor (Clf) A and B, it did show that the BIAI isolates encoded six genes with other roles in virulence that were absent in the JE2 strain, including the capsule genes cap8H , cap8I , cap8J , and cap8K ; superantigen staphylococcal enterotoxin C (SEC); and staphylococcal enterotoxin-like type L ( selL ) ( 42 , 53 ). It remains unclear whether any of these genes might contribute to the increased biofilm formation following exposure to TAPI in the presence of human plasma observed with the BIAI isolates or whether other unidentified factors are responsible.…”
Section: Resultsmentioning
confidence: 99%
“…Different types of host cell and tissue damage may be clinically apparent and are so characteristic that the identity of the invading organism may be suspected prior to culture confirmation. For example, Staphylococcus aureus typically adheres to the host (Berry et al., 2022) and produces degradative enzymes (Guerra et al., 2017; Liu et al., 2023) such as protease, coagulase, lipase or DNAase (Deplanche et al., 2019) resulting in focal tissue necrosis apparent as abscess formation, generally localized despite hyaluronidase production, with contained pus. Streptococcus (Kotb et al., 2002) by contrast produces a different clinical picture as spreading enzymes typically manifest as cellulitis with widespread fluid extravasation, initially clear and later cloudy often described as dishwater pus.…”
Section: Microorganisms and Pathogenic Mechanismsmentioning
confidence: 99%